Wood Decomposition After an Aerial Application of Hydromulch Following Wildfire in a Southern California Chaparral Shrubland - Jurgensen, Martin F.; Miller, Chris A.; Page-Dumroese, Deborah S. (Frontiers in Forests and Global Change, 2020)
Severe wildfire can affect many soil properties, and organic mulches are often applied to the soil surface to mitigate these changes and reduce erosion, particularly on steep slopes. After the southern California Cedar Fire burned 110,000 ha in 2003, hydromulch was applied to reduce sediment losses. In 2004 we established a study to assess the effect of hydromulch on organic matter decomposition at the soil surface and in the mineral soil using aspen (Populus tremuloides Michx.) and pine (Pinus taeda L.) wood stakes as standard substrates. Mass loss of both aspen and pine stakes in this dry Mediterranean ecosystem was lowest on the soil surface and increased with mineral soil depth. Wood stake decomposition appeared to be lower in the hydromulched soil than in the untreated control, but variability of subterranean termite activity in study replicates and the possible loss of hydromulch soon after application make this result questionable. Termites were clearly shown to have a major role in belowground wood decomposition, and could affect slope stability after wildfire. They also should be considered in planning OM decomposition studies in soils where they are present.